The Pushback Against Canada’s Carbon Pricing System: A Case Study of Two Canadian Provinces, Saskatchewan and Nova Scotia - Larry Hughes; Sarah Landry (Energies)
As part of its plan to transition to an energy secure and environmentally sustainable future, Canada has had a national carbon pricing system since 2019. When first introduced, the $20 (‘$’ refer to Canadian dollars (CAD) in this paper) per tonne price was widely accepted by most Canadians and seen as a way of helping Canada meet its emissions reduction pledges made at the 2015 United Nations Climate Change Conference (COP 21) in Paris. The Canadian system is novel in that it both charges consumers for their emissions and reimburses them for their expected emissions; this is intended to raise awareness of their emissions and encourage those who can afford to opt for lower-emissions energy services to do so. By 2023, the combination of the carbon price reaching $65 per tonne and the post-pandemic economic slowdown was seized on by numerous politicians as a way of pushing back against the carbon pricing system, with most demanding the entire system be scrapped. The debate intensified in late 2023 and into 2024, when the federal government removed the carbon tax on home heating oil because the reimbursement was insufficient to cover the cost of the tax. In this paper, we consider the recent actions of two Canadian provinces, Saskatchewan and Nova Scotia, embroiled in the federal carbon pricing system debate due to the removal of the carbon tax on fuel oil for space heating. The objective of this paper is to identify how some of the reasons, including global post-pandemic inflation and other challenges facing Canadians, such as those cited in third-party polls, have contributed to a rise in the system’s unpopularity. Our method estimates and compares the impacts of the carbon tax on the household energy services for space and water heating, lighting and appliances, and private (i.e., household) transportation for different types of housing (apartment, single-attached, and single-detached) and number of occupants (two, three, and four) in Saskatchewan and Nova Scotia. The results of this work show that while Saskatchewan households have higher energy intensities than those in Nova Scotia, the impact of the carbon tax on Nova Scotians using fuel oil for heating was greater than in Saskatchewan. In Saskatchewan and Nova Scotia, natural gas and electricity, respectively, are used for heating. This paper concludes with a summary of our findings and potential options for improving perceptions of the system.